2021
DOI: 10.1364/oe.436030
|View full text |Cite
|
Sign up to set email alerts
|

Pulse evolution and multi-pulse state of coherently coupled polarization domain walls in a fiber ring laser

Abstract: Pulse evolution and multi-pulse state of coherently coupled polarization domain walls (PDW) is experimentally demonstrated in a novel fiber ring laser. Versatile pulse shapes benefit by wide range moving of PDW in the weakly birefringent fiber. The 8.6 m short-cavity structure is more compact and accessible based on a 976 nm pump with nearly zero negative dispersion (-0.0002 ps2). Besides, multi-pulse patterns such as PDW splitting, harmonic mode-locking, and periodic soliton collision are also observed under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…More recently, Zhu et al demonstrate spectrally flat high-power mid-IR SC generation with record-breaking power of 33.1 W and spectral ranges of 1.9-4.02 μm by a Tm 3+ -doped fiber amplifiers with repetition rate of 4.08 MHz, demonstrating the advantages of 2 μm noiselike pulse pump in high-power mid-IR SC generation. [296]…”
Section: Mid-ir Supercontinuum Generationmentioning
confidence: 99%
“…More recently, Zhu et al demonstrate spectrally flat high-power mid-IR SC generation with record-breaking power of 33.1 W and spectral ranges of 1.9-4.02 μm by a Tm 3+ -doped fiber amplifiers with repetition rate of 4.08 MHz, demonstrating the advantages of 2 μm noiselike pulse pump in high-power mid-IR SC generation. [296]…”
Section: Mid-ir Supercontinuum Generationmentioning
confidence: 99%
“…The typical feature of such pulses is that the polarization of light is periodically switched between two orthogonal directions at round-trip frequency. And for practical applications, PDs were studied to achieve the square-shaped pulse [15][16][17][18][19] and have been used in optical fibers as topological bits for data transmission [23] . Due to the existence of birefringence in fiber, the fundamental mode contains two orthogonal polarization modes with different propagation constants.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the existence of birefringence in fiber, the fundamental mode contains two orthogonal polarization modes with different propagation constants. PDW pulses are obtained due to the cross coupling of the two orthogonal polarization modes [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . In 2009, Zhang et al [6] first experimentally observed PDW solitons in weakly birefringent cavity fiber lasers, which were formed due to the strong coherent cross-polarization coupling of light in the fiber lasers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical soliton in optical fiber has already been studied by many researchers during past decades [1][2][3][4][5][6][7][8][9]. Commonly, optical soliton can be formed in an anomalous dispersion regime under the balance between group-velocity dispersion and self-phase modulation.…”
Section: Introductionmentioning
confidence: 99%